Effect of Enhanced Recovery After Surgery Protocol Implementation on Cost and Outcomes by Type of Colectomy Performed. Issue 9 (September 2020) - Landry, Miles; Lewis, Rachel; Antill, Andrew; Eric Heidel, R.; Taylor, Jessica; Casillas, Mark A.; Russ, Andrew J.; Daley, Brian; McLoughlin, James
Background: Enhanced recovery after surgery (ERAS) protocols are widely utilized for elective colorectal surgery to improve outcomes and decrease costs, but few studies have evaluated the impact of ERAS protocols on cost with respect to anatomic site of resection. This study evaluated the impact of ERAS protocol on elective colon resections by site and longitudinal impact over time. Methods: A single-center retrospective cohort study of 598 consecutive patients undergoing elective colorectal resection before and after implementation of ERAS protocol from 2013 to 2017 was performed. The primary outcomes were length of stay (LOS) and cost. Comparative and multivariate inferential statistics were used to assess additional outcomes. Results: A total of 598 patients (100 pre-ERAS vs 498 post-ERAS) were evaluated with an overall median LOS of 4 days for right and left colectomies and 3 days for transverse colectomies. When comparing type of resection before and after ERAS protocol introduction, an increased LOS for left hemicolectomies from 3.09 to 4.03 days ( P = .047) was noted, with all other comparisons failing to reach statistical significance. Over time, an initial decrease in LOS for MIS approach after protocol introduction was observed; however, this effect diminished in the ensuing years and had no significant effect overall. Total cost of care was significantly increased post-ERAS for all cohorts except transverse colectomies. No further statistically significant differences were found. Conclusion: After an initial improvement in outcomes, continued utilization of ERAS protocols demonstrated no improvement in LOS compared to pre-ERAS data and increased cost overall for patients regardless of site of resection.